2017
DOI: 10.1186/s12917-017-1038-z
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of virus neutralizing antibodies for rabies in different groups of dogs following vaccination

Abstract: BackgroundMass vaccination of dogs is considered fundamental for national rabies control programmes in Sri Lanka, as dog is the main reservoir and transmitter of the disease.MethodsDogs were followed to determine the sero-prevalence of antibodies to the rabies virus. Altogether 510 previously vaccinated and unvaccinated dogs with owners (domestic dogs) and dogs without owners (stray dogs) of the local guard dog breed in different age groups recruited from Kalutara District, Sri Lanka. The dogs were vaccinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Rabies virus is a neurotropic, negative sense, single-stranded RNA virus that belongs to the family Rhabdoviridae, genus Lyssavirus [ 1 ]. The causative virus can spread from saliva of infected animals to others through neuromuscular route [ 2 ]. It has been reported that around 55,000 human deaths occur due to rabies infection out of the millions exposed each year worldwide [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rabies virus is a neurotropic, negative sense, single-stranded RNA virus that belongs to the family Rhabdoviridae, genus Lyssavirus [ 1 ]. The causative virus can spread from saliva of infected animals to others through neuromuscular route [ 2 ]. It has been reported that around 55,000 human deaths occur due to rabies infection out of the millions exposed each year worldwide [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This proportion is far higher than other reports from similar studies. [40][41][42] This is not only a concern for rabies control efforts in the canine population but also increases the risk of rabies in humans who may not seek post-exposure prophylaxis after a bite from a vaccinated dog. It is crucial that vaccines selected for use by the veterinary public sector and for mass dog vaccination campaigns are of high quality and retain potency until administration.…”
Section: Discussionmentioning
confidence: 99%
“…At current levels of vaccine production and the financial resources committed, Wallace et al (2017) estimate a vaccine shortfall of 7.5 billion doses and a resource gap of US$ 3.9 billion to achieve global dog rabies elimination by 2030 (Wallace et al 2017). This analysis also does not take in to account that a substantial proportion of unowned dogs may fail to sero-convert to the required protective antibody levels with a single dose of vaccine (Pimburage et al 2017). It therefore becomes imperative to not lose focus on effective and long-term solutions to dog population management.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing world, a large proportion of the dog population is mostly free-roaming; these dogs are quasiowned, never restrained nor subject to health or fertility control interventions. In such populations, there is a variation in antibody response to a single dose of anti-rabies vaccine, but most dogs do not have a protective antibody titer after a year (Pimburage et al 2017).…”
Section: Update-immune-statusmentioning
confidence: 99%